Metacognitive knowledge monitoring under assessment of educational achievements - Fomin A.E., (Психологическая наука и образование (2007. Online), 2015)
We present an empirical study, which tested the hypothesis about the impact of the situation of educational achievements assessment on metacognitive monitoring of students’ subject knowledge test performance. On a sample of 47 people (21 girls, 26 boys, mean age 15.5 years) we revealed that the characteristics of metacognitive monitoring (self-decision and the accuracy of metacognitive judgments) differ in a situation of educational achievements assessment and in its absence. We found that students with high and low achievement motivation show different metacognitive monitoring of the situation in the presence or absence of the estimation of educational achievements (p < 0,05). In conclusion, we discuss the use of the data and findings in the general psychological and psycho-pedagogical studies of metacognition, and in teaching practice